Short Communication - Current status of Blastocystis in cockroaches - M.T., Farah Haziqah; M.N., Nur Asyiqin; M.K.N., Mohd Khalid; K., Suresh; A., Rajamanikam; P., Chandrawathani; S.N., Mohd Zain (Malaysian Society of Parasitology and Tropical Medicine, 2017)
There are few reports on Blastocystis spp. infections in invertebrate hosts namely, cockroaches. Due to their close proximity to humans especially to their dwellings prompted this study as these organisms could possibly play a role in human transmission. A total of 151 cockroaches consisted predominantly of nymph and adult stages were captured from several types of dwellings in the state of Perak and Selangor, Malaysia. Approximately half (40.4%) of the cockroach intestinal contents screened were positive and were found associated to two main factors, host-stage and types of dwellings. The granular and vacuolated forms were the most common cell form found in the in vitro cultures and were morphologically similar to B. hominis. However, the surface coat observed was thick with an electron lucent area observed in the central vacuole. The isolates grew in room temperature but optimal growth was observed at a 24ºC similar to the reptilian Blastocystis with a high number of cells were recovered. Using the DNA barcoding method, two isolates were identified as ST3 (allele 56), one isolate was consider as the new subtype with close relation to allele 114